2020
DOI: 10.1002/jcp.29686
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acute stress disorder on gallbladder interstitial cells of Cajal

Abstract: Physical and psychological stress exerts a substantial effect on gastrointestinal motility disorders, where trauma enhances symptoms of digestive dysfunction. Interstitial cells of Cajal (ICCs) act as pacemakers for gastrointestinal motility regulation and are likely important in stress‐associated gastrointestinal motility disorders. This study explored the mechanisms underlying gallbladder ICCs function under acute stress conditions using a rabbit chest puncture and cholecystectomy model. The stem cell factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The key characteristics and unknown details of the event itself can increase people's uncertainty about the causes of the public health event and the means to deal with it; thus, they are prone to experiencing stress manifesting as anxiety, fear, and other emotions (Main et al 2011). At the same time, severe psychological stress can cause sleep disorders, physical discomfort, and other consequences in individuals (Gao et al 2020;Huang et al 2020b). University students are in a critical period of their lives, forming an outlook on the world, life, and values; therefore, public events of a large scale could have complex and profound multiple effects on their physical and mental health (Al-Hazmi et al 2018;Huang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key characteristics and unknown details of the event itself can increase people's uncertainty about the causes of the public health event and the means to deal with it; thus, they are prone to experiencing stress manifesting as anxiety, fear, and other emotions (Main et al 2011). At the same time, severe psychological stress can cause sleep disorders, physical discomfort, and other consequences in individuals (Gao et al 2020;Huang et al 2020b). University students are in a critical period of their lives, forming an outlook on the world, life, and values; therefore, public events of a large scale could have complex and profound multiple effects on their physical and mental health (Al-Hazmi et al 2018;Huang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2020; Huang et al . 2020b). University students are in a critical period of their lives, forming an outlook on the world, life, and values; therefore, public events of a large scale could have complex and profound multiple effects on their physical and mental health (Al‐Hazmi et al .…”
Section: Introductionmentioning
confidence: 99%
“…46,47 Inhibition of SCF/c-Kit pathway was demonstrated to be associated with reduction of ICC in some disease. 35,36,39 On the contrary, improvement of SCF/c-Kit pathway help ICC recovery. 14,38 In the present study, we also found the reduction of SCF expression in colonic smooth muscles of either stressin1 or sauvagine-treated mice, which may be responsible for the reduction of ICC in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 As mentioned above, stress can induce gastrointestinal motility disorder through CRF/CRF receptor pathway while evidence also showed that acute stress could induce a reduction of ICC through SCF/c-Kit pathway in gallbladder. 39 Consequently, we are wondering if stress could affect ICC though CRF/CRF receptor resulting in gastrointestinal dysmotility. In the present study, we used mice injected intraperitoneally (ip) with two CRF receptor agonists to mimick stress and explored the mechanism of stress-induced colon motility disorder by focusing on the relationship between CRF receptor and ICC in murine colon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation